Compliant Volcanic Arc and Backarc Crust in Southern Kurile Suggested by Interseismic Geodetic Deformation. Issue 21 (3rd November 2019) - Itoh, Yuji; Wang, Kelin; Nishimura, Takuya; He, Jiangheng
Abstract: In southern Kurile, interseismic contraction observed with Global Navigation Satellite Systems is faster in the volcanic arc than in the forearc. Here, we use a viscoelastic finite element model to investigate the physical process responsible for the localized deformation. On the basis of thermal and seismic observations that suggest the volcanic arc and backarc to be more compliant than a typical continental lithosphere, we assume a lower rigidity and/or smaller thickness for the arc and backarc. We find that the interseismic observations require the volcanic arc to be very compliant and the backarc to be moderately compliant. The trade‐off between lower rigidity and smaller thickness cannot be resolved by interseismic observations alone, but coseismic observations can help to set a lower limit for the rigidity. Our results indicate that properly accounting for the long‐wavelength lithospheric heterogeneity is important to accurately inferring megathrust locking state from geodetic observations. Plain Language Summary: When the megathrust of a subduction zone is locked, the neighboring crust is shortened like a spring to build up energy for future earthquakes. GPS monitoring of the rate of shortening helps us identify the locked zone. In Hokkaido, however, the rate of shortening is larger in the area hosting a chain of volcanoes, called the volcanic arc. To explain what amplifies the shortening rate, we use computer models to investigate the effect of the lateral variations in the properties of the crust. We find that the faster shortening occurs because the arc area, and to a lesser degree the area farther away from the trench, is more compliant, that is, it offers less resistance to the lateral compression due to megathrust locking. The greater compliance is consistent with what can be inferred from heat flow and seismic imaging in this area. Our results indicate that, in order to accurately infer megathrust locking from GPS observations, we must include the greater compliance in our model. Key Points: Interseismic GNSS velocities in southern Kurile suggest low rigidity and/or thin lithosphere in the arc and, to a lesser degree, backarc Interseismic data cannot resolve trade‐off between rigidity and thickness, but coseismic data provide additional constraints on rigidity Addressing the effect of compliant arc‐back area will greatly improve the estimate of megathrust locking state